Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1, \(\sqrt{\frac{-12}{x-5}}\) xác định khi \(\frac{-12}{x-5}\) \(\ge\) 0
→x-5<0→x<5
3. xác định khi x-2>0 →x>2
5.xác định khi \(\frac{4x-5}{x+2}\ge0\)và x\(\ne\)-2
→\(\left[\begin{array}{nghiempt}\hept{\begin{cases}4x-5< 0\\x-3< 0\end{array}\right.\\\hept{\begin{cases}4x-5\ge0\\x-3>0\end{array}\right.\end{cases}\Rightarrow\left[\begin{array}{nghiempt}\hept{\begin{cases}x< \frac{5}{4}\\x< 3\end{array}\right.\\\hept{\begin{cases}x\ge\frac{5}{4}\\x>3\end{array}\right.\end{array}\right.}\)
a: \(A=\sqrt{5}-\sqrt{3-\sqrt{\left(2\sqrt{5}-3\right)^2}}\)
\(=\sqrt{5}-\sqrt{3-2\sqrt{5}+3}\)
\(=\sqrt{5}-\sqrt{5}+1=1\)
b: \(B=\sqrt{b-1}+\sqrt{b\left(b-1\right)}+\sqrt{b\left(b-1\right)}=\sqrt{b-1}\left(2\sqrt{b}+1\right)\)
Trả lời:
a, \(2\sqrt{45}+\sqrt{5}-3\sqrt{80}\)
\(=2\sqrt{3^2.5}+\sqrt{5}-3\sqrt{4^2.5}\)
\(=2.3\sqrt{5}+\sqrt{5}-3.4\sqrt{5}\)
\(=6\sqrt{5}+\sqrt{5}-12\sqrt{5}=-5\sqrt{5}\)
c, \(\left(\frac{3-\sqrt{3}}{\sqrt{3}-1}-\frac{2-\sqrt{2}}{1-\sqrt{2}}\right):\frac{1}{\sqrt{3}+\sqrt{2}}\)
\(=\left[\frac{\left(3-\sqrt{3}\right)\left(\sqrt{3}+1\right)}{3-1}-\frac{\left(2-\sqrt{2}\right)\left(1+\sqrt{2}\right)}{1-2}\right].\left(\sqrt{3}+\sqrt{2}\right)\)
\(=\left(\frac{3\sqrt{3}+3-3-\sqrt{3}}{2}-\frac{2+2\sqrt{2}-\sqrt{2}-2}{-1}\right).\left(\sqrt{3}+\sqrt{2}\right)\)
\(=\left(\frac{2\sqrt{3}}{2}+\sqrt{2}\right).\left(\sqrt{3}+\sqrt{2}\right)\)
\(=\frac{2\sqrt{3}+2\sqrt{2}}{2}.\left(\sqrt{3}+\sqrt{2}\right)\)
\(=\frac{\left(2\sqrt{3}+2\sqrt{2}\right)\left(\sqrt{3}+\sqrt{2}\right)}{2}=\frac{6+2\sqrt{6}+2\sqrt{6}+4}{2}=\frac{10+4\sqrt{6}}{2}=5+2\sqrt{6}\)
Bài 1 :
\(a,2\sqrt{50}-3\sqrt{72}+\sqrt{98}=2\sqrt{2.25}-3\sqrt{2.36}+\sqrt{2.49}=10\sqrt{2}-18\sqrt{2}+7\sqrt{2}\) = \(-\sqrt{2}\)
\(b,\sqrt{\left(3-\sqrt{5}\right)^2}-\sqrt{\left(\sqrt{5}-\sqrt{7}\right)^2}+\sqrt{28}\) = \(\left|3-\sqrt{5}\right|-\left|\sqrt{5}-\sqrt{7}\right|+\sqrt{7.4}=3-\sqrt{5}-\sqrt{5}+\sqrt{7}+2\sqrt{7}=3-2\sqrt{5}+3\sqrt{7}\)
\(c,\sqrt{7-4\sqrt{3}}+\sqrt{7+4\sqrt{3}}=\sqrt{3-2.2\sqrt{3}+4}+\sqrt{3+2.2\sqrt{3}+4}=\)\(\sqrt{\left(\sqrt{3}-2\right)^2}+\sqrt{\left(\sqrt{3}+2\right)^2}=\left|-\left(2-\sqrt{3}\right)\right|+\left|\sqrt{3}+2\right|=2-\sqrt{3}+\sqrt{3}+2=4\)
Bài 1:
a: ĐKXĐ: x>0; x<>1
b: \(A=\left(\dfrac{1}{\sqrt{x}-1}+\dfrac{1}{\sqrt{x}+1}\right)\cdot\left(1+\dfrac{1}{\sqrt{x}}\right)\)
\(=\dfrac{\sqrt{x}+1+\sqrt{x}-1}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}\cdot\dfrac{\sqrt{x}+1}{\sqrt{x}}=\dfrac{2}{\sqrt{x}-1}\)
c: Thay \(x=6+2\sqrt{5}\) vào A, ta được:
\(A=\dfrac{2}{\sqrt{5}+1-1}=\dfrac{2\sqrt{5}}{5}\)
d: Để |A|>A thì A>0
=>\(\sqrt{x}-1>0\)
hay x>1
\(\dfrac{\sqrt{12}-\sqrt{18}}{\sqrt{6}-3}-\dfrac{2\sqrt{6}-4}{\sqrt{3}-\sqrt{2}}=\dfrac{\sqrt{2.6}-\sqrt{2.9}}{\sqrt{6}-3}=\dfrac{\sqrt{2}\left(\sqrt{6}-3\right)}{\sqrt{6}-3}=\sqrt{2}\)
\(\dfrac{2\sqrt{6}-4}{\sqrt{3}-\sqrt{2}}=\dfrac{2\sqrt{2.3}-\sqrt{2.8}}{\sqrt{3}-\sqrt{2}}=\dfrac{2\sqrt{2}\left(\sqrt{3}-\sqrt{2}\right)}{\sqrt{3}-\sqrt{2}}=2\sqrt{2}\)
Vậy \(\dfrac{\sqrt{12}-\sqrt{18}}{\sqrt{6}-2}-\dfrac{2\sqrt{6}-4}{\sqrt{3}-\sqrt{2}}=\sqrt{2}-2\sqrt{2}=-\sqrt{2}\)
\(\sqrt{11+4\sqrt{7}}+\dfrac{2+\sqrt{2}}{\sqrt{2}+1}=\sqrt{\left(2+\sqrt{7}\right)^2}+\dfrac{\sqrt{2}\left(\sqrt{2}+1\right)}{\sqrt{2}+1}=2+\sqrt{7}+\sqrt{2}\)
Vậy \(\sqrt{11+4\sqrt{7}}+\dfrac{2+\sqrt{2}}{\sqrt{2}+1}-\dfrac{3}{\sqrt{7}-2}=2+\sqrt{7}+\sqrt{2}-\dfrac{3}{\sqrt{7}-2}=\dfrac{\sqrt{2}\left(\sqrt{7}-2\right)}{\sqrt{7}-2}=\sqrt{2}\)